El llamado mobing o forma de hostigamiento laboral aplicado para despedir al trabajador, debe ser tipificado y penalizado en el código orgánico integral penal ecuatoriano, por tratarse de una conducta de destrucción de la personalidad, de violación de la seguridad y estabilidad laboral del trabajador - Paladines Villavicencio, Luis Ernesto (2014)
In an organization of work implies that workers organizing, with a common purpose, such as the complying with the social objective, in which the relationship to be established between individuals and groups and groups of workers is contemplated that perform the task at hand; however, the existence of other types of relationships, other than purely productive, among individuals in a company as well as the formal development of all relationships in general is something that is fighting between these groups as superior among yes, being employees of the same company, and that there is always some resistance among field workers and office. As a result, the differentiation between groups of workers may prove inconvenient there between and abnormal functioning of social organization, which can lead to harmful consequences that go beyond simple discussions or personal problems, the existence of problems in these areas is related to the occurrence of certain dysfunctions that will impact both on workers (bad work environment, job satisfaction, motivation) on the functioning of the company (absenteeism, work stoppages, increased accidents, decreased amount and the quality of work), ie there is abandonment by the employer or by the institutions of the state in relation to the administration and the most important rapprochement between managers and workers, because the removal of the employer or the State of workers, means a form of discrimination, as expressed by workers Dam Coca Codo No Cler, who after the accident spoke to were treated despotically and who denounced should be fired, which means the application of Mobbing labor. This set of problems arising from the relationships established among workers in a labor organization have been conceptualized under the name of mobbing, this concept refers to situations of psychological harassment that occurs between members of a labor organization although to be this kind of problems of social organizations, may occur in areas other than labor, such as family, school, neighborhood, etc. To all know that today that human capital is a factor that can determine the success or failure of public and private organizations, however, the administration of public and private organizations in the XXI century still unable to resolve old problems related to negative behaviors of people who work in them; because the mobbing, also known as mobbing, which consists of an individual or group behavior in which relations of harassment between two or more members of a team, this situation creates a climate of hostility and establishing violence between bully and victim difficult and can become irreversibly impair the good performance and health of workers. In general bullying is a form of aggression that helps create a work environment that is not conducive to the good performance of the organization, it is a complex phenomenon that combines different psychological, social, ethical and legal factors with cultural, economic impact and policy, which has always been present in humanity since private property was established because since then the rich and the poor and the domination of one over the other, since humanity has gone through different stages and processes were established submissions, of which the dispossessed have found it difficult to break free. Therefore, I personally think that to know for sure the problem must consider the psychological characteristics of individuals and which are inherent in the organization to which they belong, as well as the social and cultural context in which the organization operates, in order to identify existing national developments surrounding this phenomenon is in force in the estates ie private and state in two business streams mobbing is applied indiscriminately and are aware of all Ecuadorians and not of this government but of the ancestors; so I consider very important to address this issue because it is a phenomenon that is in force.